E0390 Relationship of no or slow reflow of patients with acute myocardial infarction after PCI with the stressing blood sugar and hs-CRP. (17th November 2010) - Peng, Wei; Qiang, Fu; Jie, Bai; Yang, Sheng; Yi, Liu; Yi, Lu
Abstract : Objective: To study releation between the stressing blood sugar and hs-CRP and the no or slow reflow occurred in patients with acute myocardial infarction after primary PCI. Methods: 253 patients be suspected STEMI with chest pain were admitted to this study, all patients were selected from heart center of our hospital and the time of D-to-B was less than 6 h. were divided into group of no or slow reflow and group of normal control according to the results of CAG. Results: 26 patients had no or slow reflow, and the stressing blood sugar, hs-CRP of group with no reflow were super to the control group obviously (p<0.05 or p<0.01). Conclusion: detection of stressing blood sugar and hs-CRP were correlated to the occuration of no or slow reflow after primary PCI, and can be used to predict the Prognosis.